2017
DOI: 10.1080/14043858.2017.1298172
|View full text |Cite
|
Sign up to set email alerts
|

Collective efficacy and arson: the case of Malmö

Abstract: The burning of cars and containers during social unrest has become a topic of both scholarly and public interest in Sweden over the past decade. Studies have suggested that social disorganization theory, or its modern expression collective efficacy, may be important for explaining why some neighborhoods experience elevated levels of arson and unrest while others do not. To date no study has explicitly studied the link between arson and collective efficacy at the neighborhood level. The present study attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…While the number of burning cars has been fairly stable at around 3500 per year, the share of burning cars deemed to have been intentionally started has increased from 12% to 38% between 1998 and 2015 (MSB 2016). It has been shown that intentional car burnings are associated with social disadvantage and segregation at the municipal level (Malmberg et al 2013) and a study of Malmö suggests that this association holds also at the neighborhood level (Gerell 2017). Another problem associated with vulnerable neighborhoods is that of foreign fighters and other forms of extremist and antagonistic groups.…”
Section: National Trendmentioning
confidence: 99%
“…While the number of burning cars has been fairly stable at around 3500 per year, the share of burning cars deemed to have been intentionally started has increased from 12% to 38% between 1998 and 2015 (MSB 2016). It has been shown that intentional car burnings are associated with social disadvantage and segregation at the municipal level (Malmberg et al 2013) and a study of Malmö suggests that this association holds also at the neighborhood level (Gerell 2017). Another problem associated with vulnerable neighborhoods is that of foreign fighters and other forms of extremist and antagonistic groups.…”
Section: National Trendmentioning
confidence: 99%
“…In particular, this has been brought up in relation to deprived neighbourhoods of Sweden where criminal networks have a large impact on local communities (Polisen, 2017(Polisen, , 2019. Compared to other urban areas in Sweden, such neighbourhoods are characterized by higher levels of fear, more open air drug markets, more burning cars, and elevated levels of gang violence in the form of shootings and explosions (Brå, 2017;Polisen, 2017;Malmberg et al, 2013;M. Gerell, 2017;Sturup, Gerell, et al, 2019a).…”
Section: Study Setting and National Contextmentioning
confidence: 99%
“…Cars that are considered to have been deliberately set on fire has increased substantially in Sweden since the late 90's. The problem is most frequent in deprived neighborhoods (Malmberg et al, 2013 ; Gerell, 2017 ). Traditionally vehicle arsons are associated with rioting, and there have been some large-scale riots with a lot of burning cars in Sweden (Hallin et al, 2010 ; De Los Reyes and Hörnqvist, 2016 ).…”
Section: Hot Spots and Hot Spot Policingmentioning
confidence: 99%